Fixed-width confidence interval for treatment difference in multinomial sampling. Issue 2 (2nd June 2021) - Bandyopadhyay, Uttam; Sarkar, Suman; Biswas, Atanu
Abstract: This article deals with fixed-width confidence intervals for the difference between two treatments with ordered categorical data. Related asymptotics are obtained. Procedures are evaluated by simulations, followed by a data illustration.